2014
DOI: 10.1049/el.2014.2733
|View full text |Cite
|
Sign up to set email alerts
|

Distributed feedback 3.27 µm diode lasers with continuous‐wave output power above 15 mW at room temperature

Abstract: GaSb-based type-I quantum well laterally coupled distributed feedback diode lasers emitting in the methane absorption band near 3.27 µm were designed and fabricated. The first-order index grating with a period of 480 nm was defined by e-beam lithography and etched on both sides of 6 µm-wide shallow ridge waveguide. Coated 2 mmlong devices demonstrated stable continuous-wave single-frequency operation in a wide temperature range with an output power of 15 mW at +17°C and 40 mW at −20°C. The Bragg wavelength tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…1 and plots the typical light-current characteristics measured for 100μm-wide ridge waveguide multimode diode lasers designed and fabricated at Stony Brook University and illustrates the generic design of the regular non-cascade laser heterostructure. Laterally coupled distributed feedback narrow ridge lasers based on non-cascade heterostructures developed at Stony Brook University and operating near 2.05 [3] and 3.27 μm [4] in CW regime at RT have been demonstrated. Several other research groups reported on efficient GaSb-based type-I QW high power and single mode diode lasers.…”
Section: Introductionmentioning
confidence: 99%
“…1 and plots the typical light-current characteristics measured for 100μm-wide ridge waveguide multimode diode lasers designed and fabricated at Stony Brook University and illustrates the generic design of the regular non-cascade laser heterostructure. Laterally coupled distributed feedback narrow ridge lasers based on non-cascade heterostructures developed at Stony Brook University and operating near 2.05 [3] and 3.27 μm [4] in CW regime at RT have been demonstrated. Several other research groups reported on efficient GaSb-based type-I QW high power and single mode diode lasers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the coincidence with one of the atmospheric spectral transmission window from 3 to 4 µm, allows also interesting applications in remote sensing and free-space optical communications [2], [3]. Conventional single-frequency sources directly emitting in this spectral region are based on semiconductor lasers, such as intercascade quantum laser [4]- [6] and lead-salt lasers [7], [8], solid-state Cr-doped chalcogenide lasers [9], and non-linear parametric sources such as optical parametric oscillators (OPOs) [10], [11] and difference frequency generation (DFG) schemes between near-infrared laser sources [12], [13]. Each of these technologies has advantages and disadvantages: the compact and robust semiconductor lasers have reduced tunability ranges and poor beam spatial qualities, the broadly tunable and narrow emission linewidth OPOs require rather complex architectures, while the simplest DFG sources have low output powers requiring high-power singlefrequency pump lasers.…”
Section: Introductionmentioning
confidence: 99%
“…For narrow shallow ridge two‐stage cascade devices emitting near 3 µm the output power in excess of 100 mW were reported [2]. Those devices were fabricated (like many others single mode GaSb‐based lasers, for instance [3]) using chlorine‐based reactive ion etching (RIE). Besides setting a new record in terms of CW output power that work also revealed an increased tendency of the GaSb‐based type‐I QW cascade diode lasers heterostructures to lateral current spreading compared with standard non‐cascade lasers.…”
Section: Introductionmentioning
confidence: 99%